Compression of Lumigraph with Multiple Reference Frame (MRF) Prediction and Just-In-Time Rendering - Zhang, Cha; Li, Jin (Data Compression Conference, 2000. Proceedings. DCC 2000, 2000)
In the form of 2D image array, Lumigraph captures the complete appearance of an object or a scene, and is able to quickly render a novel view independent of the scene/object complexity. Since the data amount of Lumigraph is huge, the efficient storage and access of Lumigraph are essential. In this paper, we propose a multiple reference frame (MRF) structure to compress the Lumigraph data. By predicting the Lumigraph view from multiple neighbor views, a higher compression ratio is achieved. We also implement the key functionality of just-in-time (JIT) Lumigraph rendering, in which only a small portion of the compressed bitstream necessary for rendering the current view is accessed and decoded. JIT rendering eliminates the need to predecode the entire Lumigraph data set, thus greatly reduces the memory requirement of Lumigraph rendering. A decoder cache has been implemented to speed up rendering by reusing the decoded data. The trade off between the computational speed and cache size of the decoder is discussed in the paper.